Iatrogenic aortic pseudoaneurysm: A forgotten complication - Almeida, S (2014)
Submitted by Helena Donato (bibliotecahvfx@gmail.com) on 2014-04-20T17:22:36Z No. of bitstreams: 1 Iatrogenic aortic pseudoaneurysm.pdf: 841871 bytes, checksum: e33c3f0c60eb116392c4d52a7b04da47 (MD5)